Allah Hadir di Mezbah Keluarga: untuk Menyelamatkan berdasarkan “Matius 1:21-24” dan Implikasinya bagi Keluarga Kristen - situmorang, wendy; Saogo, Isal; Salabbaet, Franciskus (MAWAR SARON: Jurnal Pendidikan Kristen dan Gereja, 2026)
The family is the first institution established by God as an expression of His love; however, the fall of humanity into sin since the time of Adam and Eve has damaged the relationship between humans and God and has impacted family life up to the present day. The phenomenon of many Christian families no longer making God the center of their lives, marked by the absence of a family altar, has resulted in weakened spirituality and direction in the lives of family members. This study aims to describe how God is present to save the family based on Matthew 1:21-24 and its implications for Christian families. The method used is a qualitative descriptive approach through literature study from relevant books and scientific journals. The results show that God's presence in the family is the core of salvation, and the establishment of a family altar is a crucial aspect in shaping spiritual life and saving Christian families.